2013
DOI: 10.1371/journal.pone.0055772
|View full text |Cite
|
Sign up to set email alerts
|

Cytosine Methylation Alteration in Natural Populations of Leymus chinensis Induced by Multiple Abiotic Stresses

Abstract: BackgroundHuman activity has a profound effect on the global environment and caused frequent occurrence of climatic fluctuations. To survive, plants need to adapt to the changing environmental conditions through altering their morphological and physiological traits. One known mechanism for phenotypic innovation to be achieved is environment-induced rapid yet inheritable epigenetic changes. Therefore, the use of molecular techniques to address the epigenetic mechanisms underpinning stress adaptation in plants i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 72 publications
0
25
0
Order By: Relevance
“…Numerous studies have shown that DNA methylation levels could be affected by plant stress in Arabidopsis , rice, pea and other plants [15-18], but few about trees. Uthup et al have reported the identification of DNA methylation patterns and their putative relationship with abiotic stress in the tree crop Hevea brasiliensis [14].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that DNA methylation levels could be affected by plant stress in Arabidopsis , rice, pea and other plants [15-18], but few about trees. Uthup et al have reported the identification of DNA methylation patterns and their putative relationship with abiotic stress in the tree crop Hevea brasiliensis [14].…”
Section: Introductionmentioning
confidence: 99%
“…Most importantly, using this method, the cytosine methylation level within the global genome and specific loci can be analyzed without advance knowledge of the DNA sequence. MSAP has been widely employed to detect cytosine methylation in various plants, such as maize (Shan et al 2013), wheat (Meng et al 2012), banana (Baurens et al 2003), and Leymus chinensis (Yu et al 2013b).…”
mentioning
confidence: 99%
“…It has been proposed that methylation alterations affect a gene's transcription, with methylation tending to repress it and demethylation to activate it (Richards, 1997;Yu et al, 2013;Nicotra et al, 2015). Of the 31 differentially methylated MSAP fragments (representing 12 classes of methylation/demethylation changes) isolated and sequenced, twelve were demethylated in the plants exposed to replanting disease, and the other 19 were methylated.…”
Section: Discussionmentioning
confidence: 99%